2006
DOI: 10.1016/j.ejpain.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation for complex regional pain syndrome: A systematic review of the clinical and cost‐effectiveness literature and assessment of prognostic factors

Abstract: SCS appears to be an effective therapy in the management of patients with CRPS type I (Level A evidence) and type II (Level D evidence). Moreover, there is evidence to demonstrate that SCS is a cost-effective treatment for CRPS type I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
176
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(190 citation statements)
references
References 52 publications
3
176
1
10
Order By: Relevance
“…In a systematic review by Taylor et al 24 totaling 500 patients in 25 case series followed for a mean of 33 months, 67% had >50% pain relief, with functional capacity and quality of life significantly improved. They also considered cost and concluded that ''.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…In a systematic review by Taylor et al 24 totaling 500 patients in 25 case series followed for a mean of 33 months, 67% had >50% pain relief, with functional capacity and quality of life significantly improved. They also considered cost and concluded that ''.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…Patients diagnosed with CRPS, FBSS (Figures 4 and 5), and PHN have shown significant success rates in pain management and cost-effectiveness associated with low rates of complications. The total pain management was rarely obtained by the use of SCS as therapy as indicated in Tables 2-4 (22,38,39,41,50,58,60,(65)(66)(67).…”
Section: Results In Pain Managementmentioning
confidence: 99%
“…In 2006, Taylor et al (39) presented the results of the systematic review and the meta-analysis of the clinical SCS cost-effectiveness in the management of CRPS patients. This study comprised 25 case series, 1 randomized controlled trial and 1 cost-effectiveness study.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 2 more Smart Citations